Is there an optimal whole-body vibration exposure `dosage` for performance improvement? - Morton, R. H.; Cochrane, D. J. (International Journal of Exercise Science, 2014)
Whole-body vibration exposure has been shown to improve performance in vertical jumping and knee extensions. Some studies have addressed the question of dose optimality, but are inconclusive and inappropriately designed. Our purpose was to more thoroughly seek an optimum combination of duration, amplitude and frequency of exposure to side-alternating whole-body vibration. We used experimental designs constructed for response surface fitting and optimisation, using both blocked and unblocked second order central composite designs with 12 participants. Immediately after each exposure a discomfort index was recorded, then peak and average torque, peak and average jump height, together with peak and average jump power were recorded over three trials both pre- and post-exposure at each treatment combination. ANOVA revealed that all performance measures improved after vibration exposure. However, no successful response surface fits could be achieved for any of the performance measures, except weakly for average jump height and average jump power for a single subject. Conversely, the discomfort index increased linearly with both vibration amplitude and frequency, more steeply as exposure duration increased. We conclude that although vibration exposure has a significant positive effect on performance, its effect is so variable both between and within individuals that no real optimum can be discerned; and that high amplitudes, frequencies and durations lead to excessive discomfort.